New distribution and host record of Stenarella insidiator (Smith, 1859) (Hymenoptera: Ichneumonidae: Cryptinae) from Vietnam - Pham, Thi Nhi; Cao Thi , Quynh Nga; Dang, Thi Hoa (Academia Journal of Biology, 2024)
The ichneumonid parasitoid Stenarella insidiator (Smith, 1859) is recorded for the first time from Vietnam based on the specimens collected from Tam Dao National Park in Vinh Phuc province, Na Hang district in Tuyen Quang province, and Bidoup-Nui Ba National Park in Lam Dong province. In addition, the wasp Orancistrocerus aterrimus (de Saussure, 1852) (Hymenoptera: Vespidae) is reported as a new host of this parasitoid. The parasitoid is described based on Vietnamese material with information of its overwintering in the wasp nest.